Examining the relationship between charismatic leadership and the lower-order factors of LMX: A follower based perspective of the moderating effect of communication frequency. Issue 8 (7th November 2016) - Salvaggio, Trent; Kent, Thomas W.
Abstract : Purpose: The purpose of this paper is to test the effects of a followers' perception of charisma to the followers' perceived quality of each of the four sub-dimensions of LMX quality, and the moderating effect of communication frequency on such a relationship. The study hopes to assess the relationship of the four sub-factors of LMX to charisma and, thereby, to advance the current understanding of relationship-based views of leadership. Design/methodology/approach: In total, 208 employed adults who are currently residing within the USA completed surveys that assessed charisma, LMX and it's sub-factors, and communication frequency. The surveys were validated and the relationships between the variables were tested using partial least squares regression. Findings: Charismatic leadership was shown to have significant effects on all the LMX sub-factors suggesting that charisma is not a simple trait possessed by some leaders. Additionally, the data suggests that there is a significant yet different level of effect of communication frequency on all the LMX sub-factors. Research limitations/implications: Implications of the research findings are discussed; however, there are some shortcomings in the research. As the variables of communication frequency and LMX quality were rated by the same individual, a limitation to this study exists by way of possible same source bias. A further limitation results from the measurement method utilized to determine communication frequency and its dependence upon the ability of the survey respondent to accurately recall this information free from any type of recall bias (Raphael, 1987). Further study needs to be done into the nature of the moderating effects present on the four lower order factors of LMX. If there are intervening factors that influence the quality of the moderating effects, such as role expectation and role congruence, then the authors may be able to gain further insight into the positive and negative nature of these moderating effects. Practical implications: The findings suggest that charisma is not a simple, one-dimensional factor and also suggests that the authors need to reconceptualize the ideas of charisma. At a minimum, the authors must rethink how to train people to become leaders. Originality/value: The study advances the understanding of the relationship between charisma and LMX and its composite factors.